Perancangan Sistem Informasi Pengelolaan Homestay: Homestay Management Information System Design - Nofri Yudi Arifin (Engineering and Technology International Journal, 2022)
This study discusses the design of homestay information systems, information systems are computer applications that are used for businesses related to the business world, especially in data and information storage and processing systems so that they can run their business easily and smoothly. Homestay is a residence where several rooms are rented out to guests for a certain period of time to learn about a particular culture or local routine. Homestay District. Batu Aji which has 21 rooms Currently in Batu Aji only about 30% of the rooms have been occupied by room tenants, since the Covid-19 pandemic and the absence of promotional media from Homestay is less well known to the general public resulting in many unfilled rooms. So it is necessary to design a system and digital information technology and are expected to be able to provide solutions to the problems that exist in homestay rentals.